Trabalho, subjetividade e processo de adoecimento: os trabalhadores de software em São Carlos-SP - Machado, Sara Luiza (2020)
The city of São Carlos-SP is a favorable environment for the installation of information technology companies, due to the presence of universities and institutes focused on technological training and the existence of coworking spaces. Regarding the IT worker, specifically that of software production, this represents a synthesis of the “new” flexible worker profile, considering the forms of organization of his work and the requirements for the exercise of the activity, which has a high demand in terms of cognitive and subjective. Thus, the objective of this work was to understand how the work process and content in the information technology segment impact the subjectivity of the workers surveyed, as well as to understand what their perception is about their own subjectivity / health. Qualitative methodology was used, especially interviews based on a semi-structured script. It is noted that there is a weakening of the limits between work and personal life, with the naturalization of carrying out work activities in moments of rest. In relation to job control, customer interference is seen as stressful, since charges are excessive and orders are not well established. Due to the pace of work, young people are considered the ideal type of worker, while aging is associated with the feeling of professional exhaustion. From the perspective that work contributes to a “greater good”, recognition is an important factor in terms of staying in the job and keeping the worker in a healthy condition. In the work environment, there are spaces that seek to add productivity with fun, seeking to propagate the “love your work” discourse. In addition, some companies, despite maintaining speeches that show concern for the mental health of workers, in practice present strict parameters of goals and results, which has important impacts on the subjectivity of professionals.